Legal Protection for Child Sexual Violence Victims: Victimology Perspectives, Challenges, and Policy Solutions in Asia - Indah Sri Utari; Ubaidillah Kamal; Diandra Preludio Ramada; Benny Sumardiana; Bhanu Prakash Nunna (Jurnal Suara Hukum, 2026)
This study critically examines the implementation and effectiveness of legal protection mechanisms for child victims of sexual violence across selected Asian-majority countries. While many nations in the region have ratified international conventions (such as the CRC) and enacted specialized domestic legislation, the reality of enforcement is often undermined by socio-cultural dynamics and systemic weaknesses. Employing a victimology framework, this research analyzes the factors contributing to revictimization and the specific challenges faced by children navigating the criminal justice system within contexts characterized by strong familial hierarchy, community privacy norms, and prevalent gender biases. The study identifies three core implementation challenges common across the region: 1) the pervasive influence of stigma and victim-blaming rooted in traditional values, leading to underreporting and case withdrawal; 2) procedural inadequacies within law enforcement and judicial sectors, resulting in non-trauma-informed practices and secondary harm; and 3) the failure to effectively deliver restitution and holistic rehabilitation services due to funding gaps and lack of integrated inter-agency cooperation. Drawing upon comparative case analysis, this paper proposes alternative solutions that are culturally sensitive yet legally robust. Key recommendations include implementing mandatory specialized judicial training focused on child psychology and trauma-informed interviews, establishing state-funded victim compensation and rehabilitation schemes independent of criminal prosecution outcomes, and promoting community-level restorative justice initiatives that prioritize the child's well-being over solely punitive measures. Ultimately, this study advocates for a paradigm shift from a purely punitive legal response to a comprehensive, victim-centered approach tailored to the unique societal structures of Asian-majority countries.